Pytania egzystencjalne we wczesnej edukacji religijnej - Maria Szczepska-Pustkowska (Problemy Wczesnej Edukacji)
The dispute on the possibility and shape of teaching religion in the public school has been going on for centuries. And although this education has found its place in school, the debate that is around them means that in the face of the challenges of pluralism, multiculturalism and multi-religiousness, it must constantly determine its status, mission, goals and tasks. There are still numerous doubts as to whether the school is at all the most appropriate place for shaping the sensitive areas of the human spirit, which is the religious worldview. The purpose of this text is to reflect on the place and role of existential questions in (Polish) early religious education. The text also asks about the dialogical nature of teaching, which is a cardinal prerequisite for philosophical inquiry in education (including religious education). For the purpose of this study, the analysis of “Basic Program of the Catechesis of the Catholic Church in Poland” from 2010 and 2018 was made.